CircSamd4 represses myogenic transcriptional activity of PUR proteins. Issue 7 (25th January 2020) - Pandey, Poonam R; Yang, Jen-Hao; Tsitsipatis, Dimitrios; Panda, Amaresh C; Noh, Ji Heon; Kim, Kyoung Mi; Munk, Rachel; Nicholson, Thomas; Hanniford, Douglas; Argibay, Diana; Yang, Xiaoling; Martindale, Jennifer L; et al.
Abstract: By interacting with proteins and nucleic acids, the vast family of mammalian circRNAs is proposed to influence many biological processes. Here, RNA sequencing analysis of circRNAs differentially expressed during myogenesis revealed that circSamd4 expression increased robustly in mouse C2C12 myoblasts differentiating into myotubes. Moreover, silencing circSamd4, which is conserved between human and mouse, delayed myogenesis and lowered the expression of myogenic markers in cultured myoblasts from both species. Affinity pulldown followed by mass spectrometry revealed that circSamd4 associated with PURA and PURB, two repressors of myogenesis that inhibit transcription of the myosin heavy chain (MHC) protein family. Supporting the hypothesis that circSamd4 might complex with PUR proteins and thereby prevent their interaction with DNA, silencing circSamd4 enhanced the association of PUR proteins with the Mhc promoter, while overexpressing circSamd4 interfered with the binding of PUR proteins to the Mhc promoter. These effects were abrogated when using a mutant circSamd4 lacking the PUR binding site. Our results indicate that the association of PUR proteins with circSamd4 enhances myogenesis by contributing to the derepression of MHC transcription.